Jenis Kesalahan Pada Pembuktian Matematis : Systematic Literature Review - Irda Aulia Hadi Lubis; Rusi Ulfa Hasanah; Khairunnisa Tanjung; Lisra Mahfirah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The aim of this Systematic Literature Review research is to find a way that can help overcome the problems faced and identify different points of view regarding the problem being researched and reveal theories that are relevant to the problems in the research. The research method used is literature study. Electronic databases used by researchers include Google Scholar, Garuda. Next, all articles are extracted and only articles that are relevant and meet the inclusion criteria will be analyzed. The results of the research suggest that the main type of error in mathematical proof is conceptualization error. Students do not understand the meaning of the questions due to a lack of basic understanding and lack of literacy to understand the meaning of the questions given. This must be explored further to strengthen understanding of concepts and mastery of techniques and strategies in mathematical proof.